The effect of sintering ramp rate on the sinterability of forsterite ceramics - Teh, Y.C.; Tan, C.Y.; Ramesh, S.; Chin, K.M.C.; Tan, Y.M.; Yap, B.K.; Aimiriyan, M. (Maney Publishing, 2014)
In the present work, pure forsterite (Mg2SiO4) powder was successfully synthesised via ball milling and subsequent heat treatment as an evident from X-ray diffraction analysis. The synthesised powder were formed by powder agglomerates that were made up of loosely packed fine particles. Then, the forsterite green bodies were sintered at 1200 and 1400 degrees C with two different ramp rates (2 and 10 degrees C per minute) via conventional pressureless sintering. No decomposition of forsterite phase was observed at both ramp rates. This study revealed that lower ramp rate (2 degrees C per minute) possessed minor improvement on the mechanical properties only at lower sintering temperature (1200 degrees C), whereas 10 degrees C per minute ramp rate gave a significant enhancement on the mechanical properties of forsterite at 1400 degrees C. A high fracture toughness of similar to 4.9 MPam(1/2) and Vickers hardness of similar to 7.1 GPa were obtained for forsterite samples sintered at 1400 degrees C with a ramp rate of 10 degrees C per minute.